THE IMPORTANCE - PERFORMANCE ANALYSIS OF GREEN PERCEIVED VALUE AND GREEN PERCEIVED RISK ON AIR CONDITIONER PRODUCT IN MANADO. - Bokko, Stefant .; Worang, Frederik G.; Rumokoy, Farlane S. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Global warming is an event where temperature of earth increases due to  emission of greenhouse gases in the atmosphere. Air conditioner (AC) is launched to the market to reduce air temperature in the room. This research aims to analyze the green perceived value and green perceived risk on Air Condtioner product in Manado. Type of this research is descriptive with quantitative approach and IPA as the measurement tool. The sample size is 100 respondents posessing an Air Condtioner product in Manado. Purposive sampling used to collect data through online questionnaires. The result for green perceived value and green perceived risk shows that those attributes are very important to the customers but the performance levels are assessed lower this attribute located in Quadrant 2. Attributes located in this quadrant means that customers already satisfied with company performance and company needs to maintain and keep this customer satisfaction. Then attributes located in this quadrant have a low importance to the customers and the company also has low performance on those attributes. So, the attributes located in this quadrant are not prior to the company but could be the concern for the customer itself, those attributes located in Quadrant 3 with low average. Keywords: importance and performance analysis, green perceived value, green perceived risk